National Goals in Foreign Policy: NGIFP - Wazir, Irfan; Wahdat, Rabani (Integrated Journal for Research in Arts and Humanities, 2022)
The basis and survival of states in foreign policy depends on national goals and interests. Guaranteeing and defining national goals for states is so fundamental and important that foreign policy has no special meaning without it. States pursue their national goals and interests seriously in their foreign policy decision-making and structuring. The national goals and interests of states are subject to variability for a variety of reasons, and uniformity is unlikely. Why some of the goals that are set for almost all states as national goals are related to the self-preservation and security of states. That security is paramount to all foreign goals in terms of degree of importance for all countries. The purpose of security is the self and the purpose of self-preservation is these four phenomena: Preservation of national territory, protect your population, protecting the independence of the country, the survival of the political and economic system.